2011
DOI: 10.1002/app.34729
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable poly(L‐lactic acid)/TiO2 nanocomposites: Thermal properties and degradation

Abstract: Poly(L-lactic acid)-titanium dioxide nanocomposites (with various loadings of TiO 2 : 0.5, 1, 2, 5, and 10 wt %) were produced by solution casting method. The influence of TiO 2 on thermal properties and crystallinity of PLA was investigated by DSC and FTIR spectroscopy. The TiO 2 nano filler has no significant influence on the characteristic temperatures (T g , T c , and T m ), but has high impact on the crystallinity of these systems. The degree of crystallinity X c significantly increases for PLA nanocompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
79
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 29 publications
11
79
1
3
Order By: Relevance
“…Moreover, at short-time exposure (50 h) the weight loss determined for all composites is lower than 1%, while for neat PLA it is 3%. In our previous studies, it was shown that the photodegradation of PLA is significantly influenced by the addition of various nanofillers, for example TiO 2 [36,37]. The stability of all talc filled samples towards UV light is certainly due to the crystalline structure induced by the presence of talc in the PLA matrix and to the photodegradation inactivity of the filler itself.…”
Section: Film Transparency and Photodegradationmentioning
confidence: 97%
“…Moreover, at short-time exposure (50 h) the weight loss determined for all composites is lower than 1%, while for neat PLA it is 3%. In our previous studies, it was shown that the photodegradation of PLA is significantly influenced by the addition of various nanofillers, for example TiO 2 [36,37]. The stability of all talc filled samples towards UV light is certainly due to the crystalline structure induced by the presence of talc in the PLA matrix and to the photodegradation inactivity of the filler itself.…”
Section: Film Transparency and Photodegradationmentioning
confidence: 97%
“…This result shows that crystallization of PLA (both primary and secondary crystallization) was completed during scaffold fabrication. The degree of crystallinity (χ c ,Table 2), calculated from the DSC curves by means of Equation increases with increasing content of TiO 2 nanoparticles in the scaffold, possibly due to an earlier reported nucleating effect of titania on PLA crystallization[27][28][29].XRD patterns of PLA and of its nanocomposite scaffolds, with distinctive crystalline peaks, are given inFigure 2. It can be observed that XRD pattern for pure PLA scaffold shows an intensive reflection at 2θ = 16.6° and a less intense peak at 2θ = 19.0°,corresponding respectively to the (110/200) and (203/113) planes of the orthorombic lattice of the α-form [30].…”
mentioning
confidence: 99%
“…587 Nanoparticles increased the degradation rate of polymer on UV exposure (365 nm). 587 Hydrolytic degradation rate was also increased with the filler content increased. 587 The enzymatic degradation was slowed down by the presence of nanofiller.…”
Section: Poly(lactic Acid)mentioning
confidence: 96%
“…587 Presence of titanium dioxide and its concentration had little influence on glass transition and melting temperatures of polymer but it influenced the degree of crystallinity. 587 Nanoparticles increased the degradation rate of polymer on UV exposure (365 nm). 587 Hydrolytic degradation rate was also increased with the filler content increased.…”
Section: Poly(lactic Acid)mentioning
confidence: 98%